Planning in Cold War Europe : Competition, Cooperation, Circulations (1950s-1970s). - Christian, Michel; Kott, Sandrine; Matejka, Ondrej (Berlin/München/Boston : Walter de Gruyter GmbH, 2018)
The peer-reviewed series offers books that illuminate the multifaceted history of the Cold War in both its European and Global dimensions, across and beyond the Iron Curtain. It focuses on the interactions, interdependencies and co-operation of Eastern state socialist countries (and their citizens) with Western capitalist, Latin American, African and non-aligned states (and their citizens), as well as with China.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books